A combined Bernoulli collocation method and imperialist competitive algorithm for optimal control of sediment in the dam reservoirs - Raheleh Khanduzi; Asyieh Ebrahimzadeh; Zahra Ebrahimzadeh (AUT Journal of Mathematics and Computing, 2024)
Reservoir sedimentation increases economic cost and overflow of dam water. An optimal control problem (OCP) with singularly perturbed equations of motion is perused in the fields of sediment management during a finite lifespan. Subsequently the OCP is transformed to a nonlinear programming problem by utilizing a collocation approach, and then we employed the imperialist competitive algorithm to improve the execution time and decision. So, the solutions of the optimal control and fast state as well as the maximization of net present value of dam operations are obtained. An illustrative practical study demonstrated that sedimentation management is economically favourable for volume of confined water and total amount in remaining storage and effectiveness of the propounded approach.